The Effect of Third-Party Funds, Capital Adequacy Ratio, Casa Ratio, Bi Rate, And Inflation Towards The Distribution of Credit Banking in Indonesia - Danang Indrajaya; Muji Astuti; Ahmad Maulidizen; Naufal Kurniawan (Yayasan Riset dan Pengembangan Intelektual, 2021)
This research aims to determine the effect of internal and external factors on bank lending. The independent variables analyzed were Third-Party Funds (DPK), Capital Adequacy Ratio (CAR), CASA ratio, BI rates, and inflation. While the dependent variable in this study is bank credit distribution. This research was conducted by taking secondary data through the publication of Bank Indonesia (www.bi.go.id), the Financial Services Authority (www.ojk.go.id), and Bureau Van Dijk (www.orbis.bvdinfo.com). The population in this study are banks listed on the Indonesia Stock Exchange (IDX). A sampling of this study was conducted using the purposive sampling method, which amounted to 15 banks with the largest assets in Indonesia in 2018. The research period used is based on annual banking reports, 2011-2018. This research is a quantitative study using the FEM (Fixed Effect Model) method. The results of this research indicate that the variable of Third-Party Funds, Capital Adequacy Ratios, CASA ratio, and Inflation is significantly effective towards the distribution of credit banking partially. On the other hand, the variable BI rate is not significantly effective to the distribution of credit banking. Meanwhile, DPK, CAR, CASA, BI rates, and inflation simultaneously have a significant effect on the distribution of credit banking.